(untitled) (Global Journal of Medical Research, 2022)
Background National Rural Health Mission NRHM provides a trained female community health worker i e Accredited Social Health Activist ASHA to every Indian village An ASHA acts as a bridge between the rural people and the health service outlets Objective The objective is to understand the knowledge levels of ASHAs regarding various aspects of maternal and child health Method This cross-sectional study conducted between April 2017 and July 2017 attempts to assess the knowledge levels of 232 ASHAs working in Ompi CHC Community Health Centre Killa PHC Primary Health Centre and Atharabula PHC These centres are located in Ompi RD Rural Development Block and Killa RD Block of Gomati District of Tripura Knowledge level is assessed by performing binomial test at 5 level of significance